Preventing phrenic nerve stimulation by a patch insulation in an intact swine heart model. - Jin-Long Huang; Yenn-Jiang Lin; Yi-Wen Hung; Yu-Cheng Hsieh; Chien-Ming Cheng; Kuo-Yang Wang (PLoS ONE, 2014)
Phrenic nerve stimulation (PNS) could be prevented by a silastic patch over the epicardial lead. We studied the effects in preventing PNS by placing a silastic patch directly over an epicardial lead or placing a graft around the phrenic nerve (PN).Fourteen Lanyu swine were enrolled. A bipolar lead was placed epicardially on the left ventricle (LV) inferior to the PN. An implantable cardioverter-defibrillator (ICD) lead was placed into the right ventricle (RV). The maximal influential distance (MID) was measured under 3 pacing configurations to express the influential electrical field on the PN. The threshold of the LV and PN were evaluated epicardially. Then, PTFE patches of different sizes (10×10 mm, 20×20 mm and 30×30 mm) were placed between the LV lead and PN to study the rise in PN threshold in 7 swine. On the other hand, the PN were surrounded by a PTFE graft of different lengths (10 mm, 20 mm, and 30 mm) in the remaining 7 swine. LV-bipolar pacing showed the shortest MID when compared to the other 2 unipolar pacing configurations at pacing voltage of 10 V. The patch was most effective in preventing PNS during LV-bipolar pacing. PNS was prevented under all circumstances with a larger PTFE patch (30×30 mm) or long graft (30 mm).PNS was avoided by placing a PTFE patch over the LV lead or a graft around the PN despite pacing configurations. Hence if PNS persisted during CRT implantation, a PTFE patch on the LV lead or a graft around the PN could be considered.